"Prevalence of chronic pain following resection of pelvic bone tumours: A single centre prospective observational survey". Issue 3 (June 2022) - Bakshi, Sumitra; Rana, Meenal; Gulia, Ashish; Puri, Ajay; Harsha, Tadala SS; Tiwari, Shashank; Gotur, Aparna
Background: Hemipelvectomy is a major surgery most often performed for pelvic malignancy. These complex surgeries often involve dissection around major neurovascular bundle and resection of tumour being bone along with involved tissues. This may result in short and long term morbidities. There is very little literature about incidence of chronic pain after pelvic resections. We conducted a prospective study at a tertiary cancer hospital to assess the prevalence of chronic pain post hemipelvectomy. Method: This is a single centre prospective observational study conducted over 30 months. Pain scores were recorded using Brief pain inventory (BPI) and pain detect questionnaire. The quality of life was assessed using musculoskeletal tumour society (MSTS) score. Intra-operative details like extent of surgical resection, nerves spared, details of intra-operative and post-operative analgesia were retrieved from the patient files. Data were analysed using SPSS 21 version. Results: Neuropathic pain post hemipelvectomy was uncommon. The prevalence of mild to moderate somatic pain was around 30%. Functional limitation was minimal as assessed by BPI and MSTS score. A high incidence of numbness was seen to persist in and around the area of surgical incision (50%). Conclusion: This is first study to report the incidence of chronic pain post hemipelvectomy done for pelvic tumour resections. Despite the extensive nature of resection involved, there is a low prevalence of neuropathic pain in this population. However, incidence of persistent somatic pain is high and there is a need for further studies for evaluating the causality